PERENCANAAN BENDUNGAN MATENGGENG DI KABUPATEN CILACAP - Frangky Arfan Pangaribuan; Bernard Septian; Sri Sangkawati; Sutarto Edhisono (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2014)
One of the efforts to develop the potency of Cijolang River is with making a dam at Matenggeng Village, Dayeuhluhur Subdistrict, Cilacap Regency. The first step to design Matenggeng Dam is hidrology analysis such as: dependable discharge, water requirement and flood discharge. The dam is projected to supply water requirement in eight subdistricts, water requirement for irrigation which has 7,175 ha of areas and hydroelectric power. Dependable discharge is Q 90%. Flood discharge plan of The Matenggeng Dam is calculated from rainfall data and the result of flow is 1,876.756 m3/s which taken from HSS Gamma 1 with Q100. Matenggeng Dam is designed with rock fill dam type. The height of the dam is 82.5 meters with slope ratio 1:2.5 at the upper course and 1:2.25 at the lower course for 50 years lifetime and storage capacity 56 million m3. The spillway design is choosen with overflow type and takes 30 m of wide with stilling basin (USBR Type II) which use 28 x 73 m as the dimension. The diversion tunnel design takes 550 m of length and 4 m of diameter. The cost of Matenggeng Dam Project is about Rp 568,959,000,000.00 (Five Hundred Sixty Eight Billion Nine Hundred Fifty Nine Million Rupiahs) with 48 weeks as time target of this project.